Effects of age and gender on upper airway, lower airway and upper lip growth - de Cassia Gonçalves, Renata [UNESP]; Raveli, Dirceu Barnabé [UNESP]; dos Santos Pinto, Ary [UNESP] (FapUNIFESP (SciELO), 2011)
The aim of the present retrospective study was to evaluate the influence of age and gender on upper and lower airway width and upper lip length. In this study, 390 lateral cephalograms were divided into 13 age groups (ranging from 6 to 18 years) and were analyzed. The intergroup differences were analyzed using a MANOVA (Multivariate Analysis of the Variance), and the intragroup differences were analyzed using an ANOVA (Analysis of the Variance) and Tukey's test. The results of the present study indicated that although the airway width and the upper lip length increased with age, the lower airway width exhibited variable growth between the ages of six and eighteen years. The airway width was significantly greater in females than males, whereas the upper airway width was similar between these two genders. The lip length was significantly shorter in females than males. The lower airway width and upper lip length were significantly different between males and females, whereas the upper airway width was similar for the genders. The upper airway width and upper lip exhibited incremental growth between the ages of six and eighteen years. The upper lip closely followed the growth pattern of the upper airway width; the growth plateaued between the ages of 6 and 9 years, increased from 9 to 16 years and plateaued from 16 to 18 years.
Keywords: Lip; Nasopharynx; Oropharynx